Professional Training of Future Teachers Based on the Principles of Decorative and Applied Art: Theoretical Aspect - Buchkivska, Galyna; Greskova, Valentyna; Krulyk, Bohdan (Pedagogical Discourse, 2023)
The article focuses on the social requirements for a modern graduate of a pedagogical institution of higher education, which include two interrelated characteristics of the professional qualities of a future teacher: a competent, initiative and creative educator; a carrier of high human culture and national identity, a specialist ready not only for effective teaching, harmonious upbringing and comprehensive development of schoolchildren but also capable to influence fundamentally the formation of spiritual and moral outlook and patriotism of pupils. The article substantiates the professional training of future teachers based on the principles of decorative and applied art, clarifies the essence, significance, psychological and pedagogical features of the educational and cognitive activity of students in the process of creative artistic and labor activity based on the principles of decorative and applied art. It is emphasized that in order to implement successfully the content of education, updated goals and objectives of the school educational components «Art» and «Technology», a modern teacher should: stand out with creativity of approaches to professional activity in general secondary education institutions, be highly qualified in the field of decorative and applied art, be aware of the educational and cultural potential of decorative and applied art and use its opportunities for teaching and upbringing schoolchildren; thirdly, should become a person of culture, a teacher-creator, and a spiritual mentor of children. The essence and significance of artistic and labor training of students based on the principles of decorative and applied art are investigated and ways to improve the professional training of future teachers are identified. The role and place of decorative and applied arts in the system of professional training of future teachers are substantiated and the main categories and concepts such as «decorative and applied art», «folk art», «folk decorative and applied art» are revealed.